Rancang Bangun Sistem Informasi Pengelolaan Aset Pada CV Sinar Baja Electric - Haribowo, Dony; Tanuwijaya, Haryanto; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
CV Sinar Baja Electric is a manufachured with Â operational activities in producing speaker. In the process of production machinery needed to support performance,cutting machine is one of the assets owned CV Sinar Baja Electric. The use of production machines that exceeds the productive age, so often a mechanical failure resulting in stoppage of production. Constraints in the management of their assets, that maintenance is performed if there is any damage, there is no schedule for asset maintenance control production machine periodically, so frequent damage and age the use of the asset becomes shorter than its economic life. Based on the above issues, was made asset management information system applications that can provide detailed information and its report of an asset management, and can perform asset management company that has been updated. The system is expected to speed up production performance.Asset management application that can provide data input engine assets more quickly and accurately, so that by the time the information needed by the user data is ready and solve the problems that companies face in providing information to those who need it accurately.